An Impact of mandibular resection guidance prostheses on oral health related quality of life (OHRQoL) - A prospective study: Impact of mandibular guidance prostheses on OHRQoL - Kalaignan, Parithimar; Ahmed, Syed Ershad (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
This prospective study was aimed to measure the impact of mandibular resection guidance prostheses on oral health-related quality of life (OHRQol). A total of 35 patients with mandibulectomy defects were included. All the patients were rehabilitated with mandibular resection guidance prostheses respectively. These patients were subjected for assessment of OHRQol. The assessment was done by using OHIP-Edent-19 and a novel scale—maxillofacial prosthesis performance scale (MFPPS). The assessment was done on all the patients at two weeks and three months of prosthesis function. The scores of OHIP-Edent, and MFPPS for mandibular resection guidance prostheses after two weeks were 33.20and 18.74 respectively. The scores of OHIP-Edent and MFPPS for mandibular resection guidance prostheses prostheses at three months were 27.71and 15.20 respectively. These findings show significant improvements of prosthesis in terms of functional, physical, psychological and social parameters after long-term follow-up (3 months).